Acorn production in Spanish holm oak woodlands - Gea-Izquierdo, G.; Cañellas, I.; Montero, G. (Forest Systems, 2008)
We present a review on the state-of-the-art of fruit prodution in Western Iberia woodlands («dehesas»), and particularly in Q. ilex (holm oak) «dehesas». This threatened ecosystem is of very high ecological and economical importance. Quercus sp. fruits (acorns) are essential for wildlife, and for pig fattening in «dehesas». In the first part of this review we briefly describe the phenology of the holm oak and the factors affecting acorn morphology and chemical composition. In the second half we analyze the main known factors reported in the literature that determine acorn production: pruning, stand characteristics, and site (weather and soil). We make several suggestions to improve future research and detect the existing gaps in the undertanding of acorn production. Fruit production is highly variable, both between and within years and individuals. The mean production in «dehesas» (mean density circa 50 trees/ha) is around 250-600 kg/ha (≈100 g/canopy-m2 , CV> 100%). Acorn morphology is also very variable, with mean sound acorn size around 3.5 × 1.6 cm, CV ≈ 10% (3.5 g/acorn, CV > 50%). Silviculture plays an essential role in acorn production. Acorn production per tree seems to be negatively related to density. The effect of pruning is less clear: production seems to be reduced in the first and second years after pruning. After the third year it is not possible to discern from the literature whether there is any response to pruning or not. Weather and soil (site) also impact production and their effects should be explored in future management. The influence of genetics is unknown and should also be addressed. Longer data series are necessary. The dasometric features of the stands need to be characterized, in order to better understand production and compare results from different locations. Much research is still required to understand the functioning of fruiting in these woodlands.
Keywords: acorn; agrosilvopastoral systems; Dehesa; fruit production; Holm oak; Quercus ilex

Acorn production in Spanish holm oak woodlands - Gea-Izquierdo, G; Cañellas, I; Montero, G (Forest Systems, 2008)
We present a review on the state-of-the-art of fruit prodution in Western Iberia woodlands («dehesas»), and particularly in Q. ilex (holm oak) «dehesas». This threatened ecosystem is of very high ecological and economical importance. Quercus sp. fruits (acorns) are essential for wildlife, and for pig fattening in «dehesas». In the first part of this review we briefly describe the phenology of the holm oak and the factors affecting acorn morphology and chemical composition. In the second half we analyze the main known factors reported in the literature that determine acorn production: pruning, stand characteristics, and site (weather and soil). We make several suggestions to improve future research and detect the existing gaps in the undertanding of acorn production. Fruit production is highly variable, both between and within years and individuals. The mean production in «dehesas» (mean density circa 50 trees/ha) is around 250-600 kg/ha (≈100 g/canopy-m2 , CV> 100%). Acorn morphology is also very variable, with mean sound acorn size around 3.5 × 1.6 cm, CV ≈ 10% (3.5 g/acorn, CV > 50%). Silviculture plays an essential role in acorn production. Acorn production per tree seems to be negatively related to density. The effect of pruning is less clear: production seems to be reduced in the first and second years after pruning. After the third year it is not possible to discern from the literature whether there is any response to pruning or not. Weather and soil (site) also impact production and their effects should be explored in future management. The influence of genetics is unknown and should also be addressed. Longer data series are necessary. The dasometric features of the stands need to be characterized, in order to better understand production and compare results from different locations. Much research is still required to understand the functioning of fruiting in these woodlands.
Keywords: acorn; agrosilvopastoral systems; Dehesa; fruit production; Holm oak; Quercus ilex